Analyzing the Relationship between Banking Performance and CSR in the Tunisian Context: A Comparative Study of Conventional and Islamic Banks - Ben Belgacem, Rania; Ben Amar , Anis; Brescia, Valerio (European Journal of Islamic Finance, 2024)
This study conducts a comparative analysis of the relationship between Corporate Social Responsibility (CSR) and financial performance in Tunisian banks. The research focuses on an extensive sample of Tunisian banks operating between 2018 and 2022. Two models are employed: one based on Return on Equity (ROE) and the other on Return on Assets (ROA). The findings reveal that Islamic banks benefit from robust CSR practices, leading to enhanced ROA and aligning with ethical principles inherent in Islamic finance. In contrast, conventional banks demonstrate no significant correlation between CSR and ROE and exhibit a negative impact of CSR on ROA. These results underscore the sector-specific nuances of CSR and its influence on financial performance, highlighting the necessity for customized CSR strategies. The study offers valuable insights for banking professionals, policymakers, and stakeholders, aiding their comprehension of the role of CSR in shaping financial outcomes in distinct banking sectors.